Does Religiosity Reduce Tax Evasion? Empirical Research Based on Gender and Education - Widiyanti Kurnianingsih; Alfriadi Dwi Atmoko (AKRUAL: JURNAL AKUNTANSI, 2022)
Tax evasion in Indonesia there are still many cases, even though the law clearly regulates taxation procedures, there are still many taxpayers who do not carry out their obligations by taking tax evasion measures. The purpose of this study was to empirically examine the effect of money ethics on tax evasion and the interaction effect of religiosity on the relationship between money ethics and tax evasion. This study also aims to test empirically the differences in the levels of the three variables based on the perspective of gender and education level. This research method uses simple regression analysis and used moderated regression analysis to test the effects of interaction and to test differences in gender perspectives and education levels on these three variables using independent sample t-test analysis. The results of this study are that money ethics has a positive effect on tax evasion, there is an interaction effect on the relationship between money ethics and tax evasion, there are differences in religiosity and tax evasion from a gender perspective, there is no difference in money ethics from a gender perspective and there is no difference in money ethics, religiosity and, tax evasion from the perspective of education level.